Evidence of patchy hydrogen reionization from an extreme Lyα trough below redshift six - Becker, George D.; Bolton, James S.; Madau, Piero; Pettini, Max; Ryan-Weber, Emma V.; Venemans, Bram P. (Oxford University Press, 2015)
We report the discovery of an extremely long (∼110 Mpc/h) and dark (τeff≳7) Lyα trough extending down to z≃5.5 towards the zem≃6.0 quasar ULAS J0148+0600. We use these new data in combination with Lyα forest measurements from 42 quasars at 4.5≤zem≤6.4 to conduct an updated analysis of the line-of-sight variance in the intergalactic Lyα opacity over 4≤z≤6. We find that the scatter in transmission among lines of sight near z∼6 significantly exceeds theoretical expectations for either a uniform ultraviolet background (UVB) or simple fluctuating UVB models in which the mean free path to ionizing photons is spatially invariant. The data, particularly near z≃5.6-5.8, instead require fluctuations in the volume-weighted hydrogen neutral fraction that are a factor of 3 or more beyond those expected from density variations alone. We argue that these fluctuations are most likely driven by large-scale variations in the mean free path, consistent with expectations for the final stages of inhomogeneous hydrogen reionization. Even by z≃5.6, however, a large fraction of the data are consistent with a uniform UVB, and by z∼5 the data are fully consistent with opacity fluctuations arising solely from the density field. This suggests that while reionization may be ongoing at z∼6, it has fully completed by z∼5.